Methodological basis for the formation of digital competence of a personnel management specialist - D. O. Ezhkov (Вестник Самарского университета: История, педагогика, филология)
The article deals with the problem of professional training of a personnel management specialist. The source base of the article was presented by pedagogical research, the object of which is the formation of professional competencies of future specialists during their studies at the university. The digitalization of the educational process necessitates a revision of the means of forming a dominant personal characteristic that contributes to the adaptation of university graduates in the professional space. The factors generating the need for digital transformation of the educational process are noted; the importance of professional competencies in a competitive environment is proved; based on the analysis of the results of pedagogical research devoted to the formation of professional competence of specialists in various fields, which concludes that it is necessary to form the digital competence of personnel management specialists, its structure is revealed.